EFEKTIVITAS NEMATISIDA DAUN JARAK PAGAR (Jatropha curcas L.) DALAM MENGHAMBAT SERANGAN NEMATODA PURU AKAR (Meloidogyne spp.) PADA TANAMAN TOMAT - Eky Santo; Djamilah Djamilah; Entang Inoriah (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2019)
[THE EFFECTIVENESS Jatropha curcas (L.) LEAF EXTRACTS IN INHIBIT ROOT-KNOT NEMATODE (Meloidogyne spp.) INJURIES ON TOMATO].  One of the main problems in tomato cultivation is the attack of root purse nematodes (Meloidogyne spp.). Some methods of controlling Meloidogyne spp. which can be done including using plants as vegetable nematicides. This study aims to get the concentration of Jatropha leaf extract which is effective in inhibiting the Meloidogyne spp attack on tomato plants. This study used 48 plants, 24 plants for observation 35 days after planting and 24 plants for observation until the age of 77 days after planting. This study used a Completely Randomized Design (CRD) with the treatment of Jatropha leaf extract concentrations (0%, 10%, 20%, 30%, 40%, 50%), and repeated four times. The results showed Jatropha curcas extract in inhibiting the attack of root purse nematodes (Meloidogyne spp.) can maintain plant height, fruit number, fruit weight, and plant stover wet weight 35 days after planting, but no significant effect on stover wet weight plants 77 days after planting and dry weight of plant stover 35 days after planting and 77 days after planting. The concentration of Jatropha leaf extract tends to increase the concentration, the smaller the rate of infection and the population of Meloidogyne spp on tomato plants. The concentration of Jatropha leaf extract 35% - 45% is the optimum concentration in inhibiting Meloidogyne spp. on tomato plants.